Improving Reading Comprehension by using Experience Text Relationship (ETR) - Astiantih, Susi; Hamid B, La Ode Muh. Idrus; Yetty; Pratiwi Sofyan, Windari Nurul (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Comprehension is the main goal of reading. Reading comprehension is an attempt to understand, evaluate, and also recognize the author’s ideas in reading text. A reader needs comprehension to catch the content of message or information from the text. One of the alternative methods to improve the students’ reading comprehension is with Experience Text Relationship method. The purpose of this study is to improve the students’ reading comprehension, by implementing Experience Text Relationship (ETR). The method in this study is  Classroom Action Research (CAR) which has several sequenced procedures including planning, action, observation, and reflection. The technique of data analysis is divided into two namely quantitative which came from the reading tests, and qualitative data which came from the observation sheets. The result of the study shows that the ETR technique is one of the most effective strategies for teaching English especially to improve students’ reading comprehension  because the students had more chance to tell their stories that might be related to the materials that were taught.